Antimicrobial effects of various platelet rich concentrates-vibes from in-vitro studies-a systematic review - Shailesh Varshney; Anshuman Dwivedi; Vibha Pandey (Elsevier, 2019)
Aim: The aim of the current review was to outline the existing information related to antimicrobial properties of various platelet concentrates, as experimented in various in-vitro studies. Background: One of the most interesting recent landmarks in the field of biological therapy has been the discovery that platelets, in addition to being capable of releasing hundreds of proteins and growth factors, can also release immunomodulatory agents with antimicrobial activity. Several international research groups have reported antimicrobial activities in both human platelets and other types of platelet rich plasma preparations. Review Result: This review was carried-out pursuing a systematic approach. An electronic search was conducted on MEDLINE and GOOGLE SCHOLAR databases using suitable search terminologies. It included preclinical studies which assessed the antimicrobial activity of Autologous Platelet Concentrates(APC).Ten in-vitro studies and one animal study, which investigated APC effects on various microorganisms, were included. Almost in all the included in-vitro studies, it was found that complete breakdown of microbial load could not be achieved by any of the APC preparations but there occurred a reduction in the growth of microorganisms. Thus APCs displayed a bacteriostatic rather than bacteriocidal activity.The only animal study included in this review which had both in-vitro and in-vivo evaluation, also showed reduction of infection caused by different microorganisms. Conclusion: Although the precise mechanism of synergy with microbial pathogens needs further validation, platelet concentrates proved to have antimicrobial properties.